Perancangan User Interface Sistem Pemesanan Makanan Warung Jimbaloka - Laurent, Valerie; Cahyadi Putra, I Gusti Ngurah Anom (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022, 2022)
In Indonesia, people often call a restaurant as a warung. Similar to restaurants, warung also provide food and drinks that can be ordered by customers. Most warung in Indonesia still use employees to do work such as taking orders and doing calculations. When the queue exceeds the limit, employees will be overwhelmed and most of them will make mistakes both in recording orders and calculating prices. To minimize those errors, the authors designed a mobile-based user interface at Warung Jimbaloka that can record orders and calculate the total price for customers. The interface design that has been made will be analyzed using the System Usability Scale (SUS) method in order to measure user’s satisfaction. The result of this study indicate that the interface design of this system is X with a value of X.